Exploring Prospective Teachers' Reasons for Choosing General Science as a Specialization - Edson Boy R. Manalansan; Marjorie A. Fogata; Danilo Jr. V. Rogayan (Universitas Pendidikan Indonesia, 2020)
Choosing a career path is difficult for students, especially in their transition from senior high school to college. Students struggle to select the most viable program that suits their interests, skills, and passion. Hence, most students end up shifting among courses and, at worst, dropping out of their program. This qualitative study explores the reasons prospective teachers specialize in General Science in a teacher education program. The data were gathered through interviews and were treated through thematic analysis. Eight themes emerged including (1) alignment to chosen senior high school strand; (2) personal choice and interest; (3) passion for science; (4) personal knowledge and skills; (5) inspiration by teachers; (6) encouragement from family; (7) challenge to oneself; and (8) non-availability of a preferred course. The study has established important implications for admission policies in terms of the selection process for students enrolling in the General Science program. Higher education institutions (HEIs) should support the continuous improvement of the science education curriculum, campus and physical facilities, and student services, which are at the heart of education in a volatile, uncertain, complex and ambiguous (VUCA) world.